High skills globalization, competitiveness, and skill formation - Brown, Phillip 1957-; Green, Andy 1954-.; Lauder, Hugh. (Oxford Oxford University Press, 2011)
Economic globalization has led to debates about competitiveness of nations. Prosperity, social justice, and welfare depend on the creation of a high-skilled workforce. This book discusses whether optimism over a future high skills economy is justified.
Electronic reproduction.
Keywords: Employment forecasting; Globalization; Skilled labor -- Supply and demand -- Forecasting